Tunneling : related party transactions of ASEAN listed firms - Juliarto, Agung (Curtin University, 2012)
Using 800 firm-year observations from five ASEAN countries 2006 – 2009 this thesis derives important insights on related party transactions to tunnel firm value from minority shareholders. Multiple regression results do not support the negative association between regulatory and competitive business environments with the extent of tunneling. There is strong evidence of a positive association between family ownership and a negative linkage between firms’ foreign ownership and tunneling. Regulators need to evolve more effective governance mechanisms.